Evaluation of tear and serum clusterin levels in thyroid ophthalmopathy patients - Balbaba, Mehmet; Ulas, Fatih; Tarim, Zehra Nur Nahirsuren; Yildirim, Hakan; Kilinc, Faruk; Ilhan, Nevin; Mizrak, Mithat (Springer, 2025)
Purpose To evaluate tear and serum clusterin levels in thyroid eye disease (TED) patients. Material and methods The study included 21 patients with Graves disease with TED, 20 patients with Graves disease without TED, and 21 healthy control subjects matched for sex and age. Clusterin and lysozyme C levels of tear and serum were detected using enzyme-linked immunosorbent assays. In addition, free triiodothyronine, free thyroxine, thyroid stimulating hormone (TSH), and autoantibody (anti thyroid peroxidase, anti thyroglobulin and TSH receptor antibody) levels were measured in all groups. Results The mean concentrations of tear clusterin and lysozyme C levels were 15.99 +/- 4.07 ng/mL and 54.54 +/- 27.58 ng/mL in Graves patients with TED, 26,28 +/- 15,98 ng/mL and 50,13 +/- 46,59 ng/mL in Graves patients without TED, and 55,53 +/- 45,99 ng/mL and 44,86 +/- 27,42 ng/mL in control subjects, respectively. The mean concentrations of serum clusterin and lysozyme C levels were 23.15 +/- 4.25 ng/mL and 93.14 +/- 51.38 ng/mL in Graves patients with TED, and 26.73 +/- 15.93 ng/mL and 74.22 +/- 55.73 ng/mL in Graves patients without TED, and 27.47 +/- 12.83 ng/mL and 76.13 +/- 65.24 ng/mL in control subjects, respectively. The tear clusterin levels showed significant differences in Graves patients with and without TED than in the control group (p < 0.001). In Graves patients with TED group, tear clusterin levels were lower than in Graves patients without TED, however this difference was not statistically significant (p = 0.431). There was a statistically significant low-grade correlation between tear clusterin and clinical activity score, retraction, and Hertel measurements (range of r value: -0.299 and -0.279, and range of p values:0.024-0.034). Conclusion The tear clusterin levels were decreased in Graves patients with and without TED. The results suggest that a local reduction in the amount of clusterin may play an important role in the pathogenesis of Graves disease and might be used as a local biomarker.
Keywords: Tear; Clusterin; Lysozyme; Thyroid autoantibodies; Thyroid eye disease